The identity of Hemeroblemma lienaris Hübner and a review of the neotropical moths of the pannosa-complex of Epidromia Guenée (Noctuidae, Catocalinae) - Becker, Vitor Osmar (2001)
Epidromia lienaris (Hübner, 1823) comb. n. is the oldest name for the species later described as E. pannosa Guenée, 1852, syn. n., E. zetophora Guenée, 1852 syn. n., Thermesia glaucescens Walker, 1858 syn. n., T. suffusa Walker, 1858 syn. n., T. tinclifera Walker, 1858, syn. n., T. lenis Walker, 1858 syn. n., T. valida (Walker, 1865) syn. n., Ophisma anlica Walker, 1865 syn. n., E. xanthogramma Wallengren, 1860 syn. n. and E. rotundata Herrich-Schaffer, 1869 syn. n.; E. poaphiloides (Guenée, 1852), is regarded the senior name for Ophiusa profana Walker, 1858 syn. n. and Remigia saluratior Walker, 1858 syn. n. Manbuta pyraliformis (Walker, 1858), comb. n. and M. nigrisparsa (Dognin, 1914), comb. n., are removed from Epidromia Guenée, 1852 and Iluza Walker, 1865 respectively.